Artificial Intelligence: Methodology, Systems, and Applications 17th International Conference, AIMSA 2016, Varna, Bulgaria, September 7-10, 2016, Proceedings - Dichev, Christo; Agre, Gennady (Lecture Notes in Artificial Intelligence,, 2016)
This book constitutes the refereed proceedings of the 17th International Conference on Artificial Intelligence: Methodology, Systems, and Applications, AIMSA 2016, held in Varna, Bulgaria in September 2015. The 32 revised full papers 6 poster papers presented were carefully reviewed and selected from 86 submissions. They cover a wide range of topics in AI: from machine learning to natural language systems, from information extraction to text mining, from knowledge representation to soft computing; from theoretical issues to real-world applications.